Interplay between Bacterial Infections and COVID-19: Mechanisms, Implications, and Management (World Journal of Experimental Biosciences, 2022)
The COVID-19 pandemic is one of the biggest changes humanity has faced over many centuries, causing health, social and economic disasters. Bacterial co-infections with COVID-19, especially respiratory tract bacteria play an important role in increasing the severity of the epidemic, increasing the mortality and morbidity rate, especially among elderly patients and immunosuppressive patients. Infection with the COVID-19 virus paves the way for the occurrence of high-risk bacterial respiratory infections caused by many species, through the effect of this virus on the immune system and the destruction of lung tissue. Immune modulation is considered one of the strategies that the body follows to confront COVID-19 infection and co-bacterial infections. That may cause affect negatively on the human body as a result of immunosuppression due to many factors, including the use of immunosuppressive drugs. The mechanism of interaction between infection with COVID-19 and co-bacterial infection is governed by several factors, including the role of the virus in paving the way for the infection to occur, in relation to its effect on the immune system directly or indirectly, in addition to the role of the virus in removing barriers to bacteria to cause infection. The use of antibiotics in an appropriate manner (not excessive) can have a positive impact on the treatment of bacterial infections associated with infection with COVID-19, as well as vaccination against some respiratory system bacteria, in addition to COVID-19. The trend in the future is to innovate ways to treat or vaccinate the cases of suffering from COVID-19 co-bacterial infections could play an important role in reducing the death rate in these cases.